2011
DOI: 10.1097/coh.0b013e32834bd257
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment for chronic hepatitis C virus/HIV-infected individuals

Sanjay Bhagani

Abstract: Peg-IFN/RBV therapy plays an important role in the management of HCV in HIV-infected patients. Efforts to maximize response to current therapy need to continue while we await new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The reason might be the combination of the high-dose recombinant adenovirus and ribavirin. The combination of ribavirin and human IFN-a protein is a common treatment method for human hepatitis C (Bhagani, 2011). Therefore, we suggest that ribavirin might interfere with the expression of porcine IFN-a in the recombinant adenovirus, or a part of ribavirin might inhibit the adenovirus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The reason might be the combination of the high-dose recombinant adenovirus and ribavirin. The combination of ribavirin and human IFN-a protein is a common treatment method for human hepatitis C (Bhagani, 2011). Therefore, we suggest that ribavirin might interfere with the expression of porcine IFN-a in the recombinant adenovirus, or a part of ribavirin might inhibit the adenovirus.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we anticipated that combination treatment using antiviral agents with different inhibition mechanisms would be more effective at circumventing FMDV resistance. Combination antiviral therapy has become standard for some human disease viruses, for example, the human immunodeficiency virus and human hepatitis C virus (Bhagani, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the known antiviral effects of IFN-α and knowledge of its dysfunction in HIV infection has led to studies investigating its use as a potential therapeutic. IFN-α has been used as therapy for HIV mono-infection, but most of the more recent studies utilizing IFN-α as a therapeutic involve patients who are HIV/HCV co-infected (reviewed in [84]). However, the first in vivo studies of IFN-α as a therapeutic were undertaken in the very early days of the pandemic, with treated Kaposi’s sarcoma (KS) patients showing tumor regression and reduced HIV p24 levels.…”
Section: Potential Therapeutic Roles Of Cytokines In Hivmentioning
confidence: 99%
“…This treatment produces rates of sustained virologic response (SVR) of around 40‐50% in patients infected with HCV genotype (HCV‐GT) 1, 60% in HCV‐GT 4, and 80% in HCV‐GT 2/3. Additionally, recent analyses have revealed that the use of pegIFNα/ribavirin in HIV/HCV‐coinfected patients may provide SVR rates which approximate those of HCV‐monoinfected patients . Current CHC therapy involves new direct‐acting antivirals plus pegIFNα/ribavirin, which has further improved the SVR rate .…”
mentioning
confidence: 99%